Histopathological Defects in Intestine in Severe Spinal Muscular Atrophy Mice Are Improved by Systemic Antisense Oligonucleotide Treatment. - Palittiya Sintusek; Francesco Catapano; Napat Angkathunkayul; Elena Marrosu; Simon H Parson; Jennifer E Morgan; Francesco Muntoni; Haiyan Zhou (PLoS ONE)
Gastrointestinal (GI) defects, including gastroesophageal reflux, constipation and delayed gastric emptying, are common in patients with spinal muscular atrophy (SMA). Similar GI dysmotility has been identified in mouse models with survival of motor neuron (SMN) protein deficiency. We previously described vascular defects in skeletal muscle and spinal cord of SMA mice and we hypothesized that similar defects could be involved in the GI pathology observed in these mice. We therefore investigated the gross anatomical structure, enteric vasculature and neurons in the small intestine in a severe mouse model of SMA. We also assessed the therapeutic response of GI histopathology to systemic administration of morpholino antisense oligonucleotide (AON) designed to increase SMN protein expression. Significant anatomical and histopathological abnormalities, with striking reduction of vascular density, overabundance of enteric neurons and increased macrophage infiltration, were detected in the small intestine in SMA mice. After systemic AON treatment in neonatal mice, all the abnormalities observed were significantly restored to near-normal levels. We conclude that the observed GI histopathological phenotypes and functional defects observed in these SMA mice are strongly linked to SMN deficiency which can be rescued by systemic administration of AON. This study on the histopathological changes in the gastrointestinal system in severe SMA mice provides further indication of the complex role that SMN plays in multiple tissues and suggests that at least in SMA mice restoration of SMN production in peripheral tissues is essential for optimal outcome.